Resilience, play and creativity: Key aspects of human development - Gianino Gadea, Lorena (2022)
The aim of this article is to make a theoretical review on resilience, play and creativity: their definitions, the main theories, their impact and evolution in the stages of life. The purpose of this bibliographic review is to know in detail of each variable, as well as to establish the relationship between them.